2017
DOI: 10.1371/journal.pone.0189261
|View full text |Cite
|
Sign up to set email alerts
|

Microbial cells can cooperate to resist high-level chronic ionizing radiation

Abstract: Understanding chronic ionizing radiation (CIR) effects is of utmost importance to protecting human health and the environment. Diverse bacteria and fungi inhabiting extremely radioactive waste and disaster sites (e.g. Hanford, Chernobyl, Fukushima) represent new targets of CIR research. We show that many microorganisms can grow under intense gamma-CIR dose rates of 13–126 Gy/h, with fungi identified as a particularly CIR-resistant group of eukaryotes: among 145 phylogenetically diverse strains tested, 78 grew … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 50 publications
3
41
0
Order By: Relevance
“…At high levels, melanin may also radiosensitize cells by producing free radicals that can interact with other cellular structures (Hill, ; Mosse et al ., ). Finally, a survey of several fungi found little correlation between melanin production and radiation resistance (Shuryak et al ., ). We suggest that, rather than melanin absorbing and protecting intracellular targets from radiation damage, that differences in experimental design such as cell culture age, growth medium and length of exposure to melanin precursors can account for many of the differences in radioresistance observed between studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…At high levels, melanin may also radiosensitize cells by producing free radicals that can interact with other cellular structures (Hill, ; Mosse et al ., ). Finally, a survey of several fungi found little correlation between melanin production and radiation resistance (Shuryak et al ., ). We suggest that, rather than melanin absorbing and protecting intracellular targets from radiation damage, that differences in experimental design such as cell culture age, growth medium and length of exposure to melanin precursors can account for many of the differences in radioresistance observed between studies.…”
Section: Discussionmentioning
confidence: 97%
“…Melanized fungi have generated interest due to their abundance in environments with high levels of background IR, which has raised the possibility of using melanin for radiation protection, or discovering a compound produced by these organisms that could prevent radiation damage or aid in recovery from radiation damage in human tissues (Dadachova et al, 2007;Cordero, 2017;Pacelli et al, 2017). Many fungi, melanized and non-melanized, are also extraordinarily resistant to acute and chronic IR, suggesting that mechanisms for radiation recovery remain to be discovered by characterizing the response to IR in these organisms (Holloman et al, 2007;Jung et al, 2016;Shuryak et al, 2017;Jiang et al, 2018;Tkavc et al, 2018). Previously, the transcriptomic responses of C. neoformans (Jung et al, 2016), W. dermatitidis (Robertson et al, 2012), S. pombe (Watson et al, 2004) and S. cerevisiae (Kimura et al, 2006) to various doses of γ-radiation have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…direct shielding) or free-radical scavenging (Dadachova et al, 2007;Schweitzer et al, 2009;Pacelli et al, 2017). Other studies have shown mixed results, with minor, inconsistent, or the complete absence of an effect of melanin on IR resistance (Pacelli et al, 2017;Shuryak et al, 2017;Schultzhaus et al, 2019c). This is not entirely surprising.…”
Section: Discussionmentioning
confidence: 99%
“…In natural microecosystems, it is widely accepted that microbial survival strategies are directed by the cooperation of different species against harsh environmental stressors, competitors, or predators (Kreft, 2004;Ö zkaya et al, 2017). Such a social activity organizes microorganisms into stratified communities, which form biofilms that improve survival (Prakash et al, 2003;Shuryak et al, 2017). The first exposure experiments in space, using microbial communities, led to the conclusion that microbial cells were better protected in space if they were living as natural assemblages embedded in rocks; for example, the endolithic phototrophic community exposed to LEO for short and long durations (Cockell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%